Relationship Between Morning Breakfast Habits, Concentration, and Biology Learning Results of Students at SMA Negeri 21 Gowa - Chacha Cahyani S; A Mushawwir Tayeb; Andi Asmawati Azis (Universitas Negeri Makassar, 2026)
Abstract. Purpose: This study aimed to examine the relationships between breakfast habits, learning concentration, and Biology learning outcomes among eleventh-grade students at SMA Negeri 21 Gowa, Indonesia.Research Methodology: A quantitative correlational research design was employed involving 119 eleventh-grade students selected through total sampling at SMA Negeri 21 Gowa, South Sulawesi, Indonesia. Data were collected using a breakfast habit questionnaire, a learning concentration questionnaire, the Concentration Grid Test (CGT), and a Biology achievement test. Statistical analysis was conducted using Pearson Product Moment correlation with the assistance of SPSS software.Results: The findings revealed a significant positive relationship between breakfast habits and learning concentration (r = 0.603, p < 0.05). In addition, breakfast habits were significantly and positively associated with Biology learning outcomes (r = 0.759, p < 0.05). Students with better breakfast habits tended to demonstrate higher concentration levels and better academic achievement in Biology.Conclusions: Breakfast habits are significantly associated with both learning concentration and Biology learning outcomes. Regular and healthy breakfast practices may support students’ cognitive readiness and academic performance.Limitations: The study employed a correlational design, which does not allow causal inferences. Furthermore, data were collected from a single school and partially relied on self-reported questionnaires, which may limit the generalizability of the findings and introduce response bias.Contributions: This study contributes to the literature on educational psychology, school health, and nutrition by providing empirical evidence of the role of breakfast habits in supporting students’ concentration and academic achievement. The findings may serve as a reference for educators, school administrators, parents, and policymakers in developing school-based nutrition and learning support programs aimed at enhancing students’ academic performance.Keywords: breakfast habits, learning concentration, Biology learning outcomes, high school students.